DSM: the company that changed itself - Fontgalland, Isabel Lausanne; de Oliveira, Matheus Santos (Revista Interface Tecnológica, 2023)
The structure- conduct-performance paradigm (ECD) was conceived more than half a century ago, in an effort to contextualize and explain the dynamics of industry, as an economic activity. Discussing Industrial Economics models is always associated with strategic decision management and technological innovation. In the study at hand, we have DSM, a global, science-based company specialized in human and animal health and nutrition. Royal DSM N.V. is a company limited by shares listed on the Euronext Amsterdam Stock Exchange, with an independent Management Board and Supervisory Board. However, the framework has also been adapted for strategic management, and in the area of strategic groups it occupies a prominent position in the literature. This study aims to address the ECD associated with DSM with the focus of marrying R&D and R&D. To this end it was made use of the methodology of case studies that responds to the diversification and mergers years out of DSM. As resultados obtidos que parte do sucesso pode ser explicado através de condutas inovadoras que focaram em sustentabilidade e fusões em conglomerado.
Keywords: DSM; ECD; R&D; Industrial Economics